OPTIMASI KONSENTRASI SUMBER KARBON DAN NITROGEN DALAM PRODUKSI BIOMASSA PICHIA SP. DENGAN METODE RESPON PERMUKAAN - Hasoloan Nainggolan, Holandres
Pichia sp. is a yeast which can be used as an inoculum in food fermentation, such as in coffee and wine industry. Therefore, the production of Pichia sp. biomass must conduct in large scale to meet the needs. The main obstacle in large-scale biomass production is the cost of yeast growth media which is economically expensive. Consequently, low-cost yeast cultivation media that have maximum biomass conversion value are needed. The main nutritional souces in increasing biomass are carbon and nitrogen, because these two compounds correlate directly with yeast growth. Organic carbon (molasses, sucrose, and dextrose) and inorganic nitrogen (ammonium), with an appropiate C: N ratio and supported by micronutrients (minerals and metals), were investigated to increase yeast growth at a relatively cheaper cost than a lab-grade synthetic media. Hence, this study aims to select carbon and nitrogen sources and determine the optimum concentration of selected carbon and nitrogen sources for Pichia sp. growth. In this research, yeast cultivation has been carried out in 100 mL working culture, pH 6, 150 rpm, 30oC, n = 3. The growth profile was observed every 4 hours for 48 hours, by calculating the specific growth rate and the amount of biomass by spectrophotometry. Selection of carbon and nitrogen sources was carried out by comparing the growth rate and biomass of Pichia sp. in a variety of carbon (molasses, sucrose, dextrose) and nitrogen nitrogen (NH4Cl, NH4NO3, (NH4)H2PO4, NH5CO3, (NH4)2SO4) with the one-factor-at-a-time (OFAT) method. The results showed that molasses (0,016±0,001 jam-1; log 8,035±0.01 sel/mL) and (NH4)H2PO4 (0,019±0,001 jam-1, log 7,936±0,228 sel/mL) were the nutrient sources which gave the highest growth rate and biomass gain of Pichia sp., so that further optimization with these compounds is carried out by the response surface methodology (RSM). Concentration optimization was carried out by comparing the specific growth rate and biomass of Pichia sp. in the concentration range of 33,5 – 67 g/L molasses and 4,5 – 9 g/L (NH4)H2PO4,. The experimental design was made using the Central Composite Experiment Design (CCD) through the Minitab. Based on this research, it was found that the optimum concentration of molasses and (NH4)H2PO4 for the growth of Pichia sp. were 66,67 g/L dan 7,17 g/L with a specific growth rate response of 0,036±0,001 jam-1 and a biomass gain of log 8,188±0,034 sel/mL